Comparative Study of Diagnostic Accuracy of Ultrasonography Vs Histopathology in patients Undergoing Hysterectomy due to Uterine Pathologies - Syed Joun Hussain Shah, Syeda Khadija-Tul-Sughra Murrium, Fatima Naveed, Mehreen Fatima, Syed Amir Gilani, Roma Babar (Pakistan Journal of Medical & Health Sciences, 2022)
Background: Accurate diagnosis of uterine pathologies has become a core part when referring patients for hysterectomy. A variety of modalities can be used for the diagnosis of uterine abnormalities. Aims: To evaluate the accuracy of ultrasound in diagnosing various uterine pathologies and to compare histopathological findings with ultrasonographical findings. Methods: A cross-sectional study was conducted on 80 females who met the inclusion criteria at Department of Gynaecology, University of Lahore Teaching Hospitalover a period of 9 months from November 2020 to August 2021. The study was started after the approval of ethical committee at the University of Lahore. All the patients were enrolled in this study after signing the informed consent form. Patients preop ultra-sonographic findings and post-operative histopathology reports of the hysterectomy was analyzed and sensitivity, specificity and diagnostic accuracy of ultrasonography for uterine pathologies was calculated. Results: Majority of the patients were in 40’s age group. Most common sonographical indication for hysterectomy was fibroids, followed byadenomyosis and endometrial hyperplasia. The overall sensitivity, specificity and diagnostic accuracy values for ultrasonography in the diagnosis of uterine abnormality was satisfactory. The diagnostic accuracy of ultrasonography in detection of uterine fibroids and adenomyosis was 96.25% and 98.75%. Conclusion: Histo-pathological analysis correlates well with the pre-operative sonographical diagnosis. The diagnostic accuracy of ultrasound in detecting intrauterine pathology urges us to utilize ultrasonography as a first-line investigation in gynaecological patients. It is a valuable adjunctive to histopatholoogy with high accuracy for identification and characterization of uterine pathologies.